Canine Bocavirus Type 2 Infection Associated With Intestinal Lesions. Issue 3 (May 2018) - Piewbang, Chutchai; Jo, Wendy K.; Puff, Christina; Ludlow, Martin; van der Vries, Erhard; Banlunara, Wijit; Rungsipipat, Anudep; Kruppa, Jochen; Jung, Klaus; Techangamsuwan, Somporn; Baumgärtner, Wolfgang; Osterhaus, Albert D. M. E.
Bocaviruses are small nonenveloped DNA viruses belonging to the Bocaparvovirus genus of the Parvoviridae family and have been linked to both respiratory and enteric disease in humans and animals. To date, 3 bocaviruses, canine bocaviruses 1 to 3 (CBoV-1–3), have been shown to affect dogs with different disease manifestations reported for infected animals. We used next-generation sequencing to identify a novel strain of canine CBoV-2 (CBoV TH-2016) in a litter of puppies that died in Thailand from acute dyspnea and hemoptysis, for which no causal pathogen could be identified in routine assays. Analysis of the complete coding sequences of CBoV TH-2016 showed that this virus was most closely related to a strain previously identified in South Korea (isolate 14D193), with evidence of genetic recombination in the VP2 gene with related strains from South Korea and Hong Kong. Use of quantitative polymerase chain reaction showed the presence of CBoV TH-2016 in several tissues, suggesting hematogenous virus spread, while only intestinal tissue was found to be positive by in situ hybridization and electron microscopy. Histologic small intestinal lesions associated with CBoV TH-2016 infection were eosinophilic intranuclear inclusion bodies within villous enterocytes without villous atrophy or fusion, similar to those previously considered pathognomonic for CBoV-1 infection. Therefore, this study provides novel insights in the pathogenicity of canine bocavirus infections and suggests that a novel recombinant CBoV-2 may result in atypical findings of CBoV infection. Although the specific cause of death of these puppies remained undetermined, a contributory role of enteric CBoV TH-2016 infection is possible.